Function of formyl peptide receptor 2 in adriamycin resistance of breast cancer - Landi Su; Jingjing Li; Li Qin; Yang Feng; Dingwen Xu (Experimental Biology and Medicine)
FPRL2 has been shown to be associated with a variety of tumours but has not been well studied in breast cancer. In this study, We combine molecular biology techniques with bioinformatics to analyze the role of FPRL2 in breast cancer and adriamycin resistance. By utilizing bioinformatics, we mine TCGA and GEO public databases to assess FPRL2 expression in breast cancer patients and its correlation with patient prognosis. Additionally, we employ the DepMap tool to probe the CCLE database, examining the relationship between FPRL2 gene effects and adriamycin sensitivity. Chemosensitivity of Adriamycin in breast cancer cells was tested by CCK-8 method. The apoptosis of breast cancer cells was determined by flow cytometry assay. Expression of p-ERK5 and p-AKT was determined by Western blot assay. Our results indicate that the expression level of FPRL2 in tumor tissues of breast cancer patients is significantly higher than that in normal tissues, and it correlates with poor prognosis in patients. Furthermore, the expression level of FPRL2 in tumor tissues of adriamycin-resistant breast cancer patients is also significantly higher than that in adriamycin-sensitive patients. The IC50 (Inhibitory Concentration 50). Of Adriamycin was significantly lower in FPRL2 silenced cells than those control cells. The apoptosis was markedly increased in FPRL2-silenced cells. p-ERK5 and p-AKT in breast cancer cells was significantly reduced after FPRL2 knocked down. In Conclusion, FPRL2 mediates Adriamycin resistance in breast cancer cells, and knockdown of FPRL2 increased apoptosis and decreased Adriamycin resistance in breast cancer cells.